2019
DOI: 10.1002/14651858.cd003983.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy for the treatment of high intracranial pressure in closed traumatic brain injury

Abstract: Decompressive craniectomy for the treatment of high intracranial pressure in closed traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 207 publications
1
70
0
3
Order By: Relevance
“… 4 Randomized controlled trials and guidelines have evaluated the benefits of DC over optimal medical treatment in cases of TBI with intracranial hypertension and recommend this procedure to improve neurologic outcomes and lower mortality rates. 4 5 6 7 Few studies in our country have issued this problem, 8 9 so we aimed to evaluate our experience of consecutive patients with severe TBI who underwent DC in our institution and analyze in-hospital mortality-associated factors.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Randomized controlled trials and guidelines have evaluated the benefits of DC over optimal medical treatment in cases of TBI with intracranial hypertension and recommend this procedure to improve neurologic outcomes and lower mortality rates. 4 5 6 7 Few studies in our country have issued this problem, 8 9 so we aimed to evaluate our experience of consecutive patients with severe TBI who underwent DC in our institution and analyze in-hospital mortality-associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recommendations by the Brain Trauma Foundation supporting the use of these therapies for sTBI, there is no level I evidence demonstrating improvement in patient outcomes through de nitive, surgical management of TBI [17,24]. DC has been performed for the purpose of relieving elevated intracranial pressure with outcome improvement in speci c TBI patients [25].DC holds the promise of reduced mortality, but long term neurological outcomes and indications remain controversial [10].…”
Section: Discussionmentioning
confidence: 99%
“…Decompressive craniectomy (DC) is a surgical procedure in which a large component of the bony skull is removed and the underlying dura mater is opened [8].Primary DC refers to leaving a large bone ap out after the evacuation of an intracranial hematoma in the early phase after a TBI [9]. DC holds the promise of reduced mortality, but long term neurological outcomes and indications remain controversial [10]. However, the indications for DC remain di cult to de ne for the surgeon in the emergency setting [11].…”
Section: Introductionmentioning
confidence: 99%
“…Experience during Operation Iraqi Freedom has indicated that decompressive craniectomy can offer an invaluable surgical technique for controlling intracranial pressure (ICP) or impending brainstem compression. [17][18][19][20][21] Decompressive craniectomy has been used in civilian GWH and seems to be of value when there is extensive hemispheric swelling that is not responsive to maximum medical management. 21 In several studies, patients underwent debridement and decompressive craniectomy.…”
Section: Surgical Managementmentioning
confidence: 99%